Challenges in managing infections among pediatric cancer patients: Suboptimal national essential medicines lists for low and middle income countries. Issue 2 (12th October 2014) - Kirby, Jeannette; Ojha, Rohit P.; Johnson, Kyle M.; Bittner, Elizabeth C.; Caniza, Miguela A.
<x xml:space="preserve">Abstract</x> Infection management for pediatric cancer patients may be compromised in low and middle income countries (LMICs) if key antimicrobials are not included in national essential medicines lists. We screened national essential medicines lists for 81 LMICs, and assessed the frequency and corresponding 95% confidence limits (CL) of countries that included the 15 International Society of Paediatric Oncology‐recommended antimicrobial agents. Only 19% (95% CL: 11%, 28%) of countries included all recommended antimicrobials in their national essential medicines lists. The selection of antimicrobial agents for national essential medicines lists in LMICs warrants attention from a pediatric cancer perspective. Pediatr Blood Cancer 2015;62:204–207. © 2014 Wiley Periodicals, Inc.